LARGE ATOMIC and NUCLEAR THREE-BODY SYSTEMS: SCATTERING and BINDING - Tomio, Lauro [UNESP]; Yamashita, Marcelo Takeshi [UNESP]; Frederico, T. (World Scientific Publ Co Pte Ltd, 2009)
The universal character of non-relativistic large three-body bosonic systems is addressed, with focus on highly interesting situations that occur in low-energy nuclear and atomic physics. Investigations on the trajectory of the first excited Efimov state, in are normalized zero-range three-body model for a system with two bound and one virtual two-body sub systems, are reported. The approach is applied to n-n-(18)C, where the n-n virtual energy and the three-body ground state are kept fixed. It is shown that the real part of the elastics wave phase-shift (delta(R)(0)) presents a zero, or a pole in k cot delta(R)(0), when the system has an Efimov excited or virtual state. A brief discussion is given on the relevance of the approach for ultracold atom physics with tunable scattering lengths.
Keywords: Few-body systems; halo features; wave equations and bound-states; Bose-Einstein condensation